Analisis Pengaruh E-Money, Jumlah Uang Beredar, Kurs dan Inflasi terhadap Pertumbuhan Ekonomi - Siregar, Rizky Azlina; Tanjung, Ahmad Albar; Sukardi, Sukardi (Universitas Batanghari Jambi, 2024)
This study aims to determine and analyze the effect of -E, money, money supply, exchange rate and inflation on economic growth in Indonesia. This study uses quantitative research methods with associative research. This study uses annual secondary data starting from August 2018 to March 2022. The population in this study is the entire growth of BPS and BI data for each variable, namely e-money from 2018-2022, money supply from 2018-2022, exchange rates and inflation from 2018-2022, and the samples in the study used the Purposive Sampling Method, namely taking samples with certain criteria. The sample in this research is 100 samples. The type of data used in this research is secondary data which is time series data in monthly intervals with the respective units of measure. JUB has a positive and significant effect on economic growth in Indonesia. Exchange rates have a positive and significant effect on economic growth in Indonesia. Inflation has a negative and significant effect on economic growth in Indonesia.